Afrikaanssprekendes, Nederlands en Afrikaans in die kerk van die provinsie Suider-Afrika - Stubbs, Jonathan Luke (Department of Religious Studies, 2026)
The aim of this study is to document the history and current status and usage of Afrikaans in the Anglican Church in Southern Africa. It is clear from the sources that the Anglican Church had contact with, and exercised some form of ministry amongst Afrikaans-spreakers from the earliest years of its presence in Southern Africa. By the 1860's and 1870's Afrikaans-speaking "mission" congregations had become a regular feature of Anglican church life. These congregations were often ministered to in "Dutch", both the standard Dutch of the Bible and various translations of the Anglican Book of Common Prayer, and the "Cape Dutch", or Afrikaans, which was their own vernacular. In the 1920's Afrikaans replaced Dutch as the vernacular church language of these congregations, and in 1925/1926 the Anglican Church published significant Afrikaans versions of the eucharistic liturgy, collects and scripture readings for Sundays, and the hymnbook. Using archival material dating from c. 1830 held by the United Society for the Propagation of the Gospel, together with church journals and published autobiographical, biographical, historical and liturgical sources, this study seeks to document the history of the use of "Dutch" (standard Dutch and "Cape Dutch") in the Anglican Church in the nineteenth century, noting the replacement of standard Dutch by Afrikaans as a vernacular language of worship in the early twentieth century, and continuing the story of Afrikaans in the Anglican Church to the 1970's. The minutes of the Provincial Afrikaans Committee provide important source material for these latter years. Together with various African languages, Afrikaans is one of the languages' vernacular in regular use in the Church of the Province of Southern Africa in the 1980's. The study thus also describes the current status and usage of Afrikaans in this multi-cultural and multi-linguistic context. Material here is based on personal observations made during a period of work in an Afrikaans-speaking parish in 1983, conversations with church members and leaders, and questionnaires circulated amongst layministers in the Diocese of Cape Town in 1983 and more widely amongst clergy in the Province in 1988. The aim of both questionnaires was to obtain an indication of the extent and manner of the use of Afrikaans as a church language in the Anglican Church. The 1983 questionnaire also sought to explore attitudes regarding the use of Afrikaans in the Church, and some consideration is given to the historical, social and political factors informing these attitudes. In conclusion note is taken of recent reinterpretations of the history of Afrikaans before 1925, and it is argued that the sources suggest a "Dutch"/Afrikaans language movement in the Anglican Church. There is also a brief reflection on the the implications of the material presented for the contemporary ministry of the Church in Afrikaans.